Revitalisasi identitas nasional DI era digital - Farhati, Liya Dwi (Maliki Interdisciplinary Journal, 2025)
The digital era has brought various new dynamics that have an impact on the existence of national identity. Advances in information technology have significantly changed the way humans interact, communicate, and build social and cultural structures. Amidst the rapid flow of information globalization, national identity faces various challenges, such as the dominance of foreign cultures, the spread of false information, and the fading collective awareness of national values. Efforts to revitalize national identity in the digital era are very important to maintain the integrity, solidarity, and character of the nation in the face of rapid changes in values. This study aims to explore various strategies and approaches in reviving the spirit of nationalism through the wise use of digital technology. Revitalizing national identity in the digital era not only requires the ability to adapt to technology, but also demands a renewal of the meaning of nationalism so that it remains contextual and relevant. By integrating technology and culture harmoniously, Indonesia has the opportunity to form a strong, open, and competitive national identity at the global level.